2020
DOI: 10.3390/antiox9100973
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Nrf2/ARE Pathway by Dietary Flavonoids: A Friend or Foe for Cancer Management?

Abstract: The nuclear factor erythroid 2-related factor 2 (Nrf2)/antioxidant response element (ARE) pathway is an important cell signaling mechanism in maintaining redox homeostasis in humans. The role of dietary flavonoids in activating Nrf2/ARE in relation to cancer chemoprevention or cancer promotion is not well established. Here we summarize the dual effects of flavonoids in cancer chemoprevention and cancer promotion with respect to the regulation of the Nrf2/ARE pathway, while underlying the possible cellular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 228 publications
(496 reference statements)
3
94
0
1
Order By: Relevance
“…These observations were reproducibly obtained in four independent experiments and further analyses of the data by densitometry revealed that the silencing of NQO2 slightly but significantly augmented the basal autophagic flux in HepG2 cells, beside preventing further LC3-II induction in response to flavones ( Figure 3 B). In addition, we observed a reproducible induction of NQO2 expression by luteolin and apigenin ( Figure 3 C), which might reflect an ARE-mediated transcriptional stimulation of NQO2 promoter by NRF2, which is a well-known effect induced by flavones on ARE-regulated phase II and antioxidant enzymes [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 86%
“…These observations were reproducibly obtained in four independent experiments and further analyses of the data by densitometry revealed that the silencing of NQO2 slightly but significantly augmented the basal autophagic flux in HepG2 cells, beside preventing further LC3-II induction in response to flavones ( Figure 3 B). In addition, we observed a reproducible induction of NQO2 expression by luteolin and apigenin ( Figure 3 C), which might reflect an ARE-mediated transcriptional stimulation of NQO2 promoter by NRF2, which is a well-known effect induced by flavones on ARE-regulated phase II and antioxidant enzymes [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 86%
“…Multiple lines of evidence recommend that polyphenolics, such as protocatechuic acid, vanillic acid, gallic acid, naringenin, 5- O -caffeoylquinic acid, catechin, taxifolin, and vicenin-2 have the capability to augment the endogenous antioxidant system, leading to cellular protection from oxidative stress [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Therefore, it is hypothesized that the augmentation of first-line antioxidant enzymes by NNSE, resulting from an abundance of phenolics and flavonoids, may contribute to the beneficial effects of NNSE against oxidative stress.…”
Section: Resultsmentioning
confidence: 99%
“…Hesperetin has been shown to attenuate damage induced by hydrogen peroxide via direct radical scavenging and by enhancing the antioxidant response via ERK/Nrf2-mediated induction of HO-1 [198]. In diabetic rats, antioxidant, anti-inflammatory, and anti-angiogenic properties of hesperetin have been reported [199]. Hesperetin significantly attenuated oxidative stress, lipid peroxidation, and ROS production in mouse brains with Aβ-induced neurodegeneration.…”
Section: Hesperetinmentioning
confidence: 99%
“…Interestingly, CGA protected against acute liver injury in animal models via activation of the Nrf2 pathway and inhibition of the NLRP3 inflammasome [186,187]. -ERK/Nrf2 Induction-ER stress protection -NF-kB modulation [198][199][200][201][202][203][204][205][206]…”
Section: Coffee Components: Caffeine and Coffee Polyphenolsmentioning
confidence: 99%